Electrical Conduction in Deuterated Ammonium Dihydrogen Phosphate Crystals with Different Degrees of Deuteration - 朱丽丽 甘笑雨 张清华 刘宝安 徐明霞 张立松 许心光 顾庆天 孙洵 (Chinese physics letters, 2015)
Conductivity measurements of deuterated ammonium dihydrogen phosphate （DADP） crystals with different deuterated degrees are described. The conductivities increase with the deuterium content, and the value of the a-direction is larger than that of the e-direction. Compared with DKDP crystals, DADP crystals have larger conductivities, which is partly due to the existence of A defects. The ac conductivity over the temperature range 25-170℃has shown a knee in the curve ofln（σT） versus T-1. The conductivity activation energy calculated by the slope of the high temperature region decreases with the deuterium content. The previously reported phase transition is not seen.